The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.4103/0972-9941.40990
|View full text |Cite
|
Sign up to set email alerts
|

Extra-biliary complications during laparoscopic cholecystectomy: How serious is the problem?

Abstract: Objective:To deteremine the incidence, nature and management of extra-biliary complications of laparoscopic cholecystectomy.Materials and Methods:This study presents a retrospective analysis of extra-biliary complications occuring during 1046 laparoscopic cholecystectomies performed from August 2003 to December 2006. The study population included all the patients with symptomatic gallstone disease in whom laparoscopic cholecystectomy was performed. The extra-biliary complications were divided into two distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
5
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 24 publications
0
18
5
2
Order By: Relevance
“…Murdock et al reported a comparable incidence of the same (1.62%) in their study. [12] This study shows the incidence of intraoperative haemorrhage as 0.92%, which is significantly lower than the study by Malik et al [13] (2.86%), but higher than study by Deziel et al (0.25%). There were no bile duct injuries in our study.…”
Section: Intraoperative Complicationscontrasting
confidence: 54%
“…Murdock et al reported a comparable incidence of the same (1.62%) in their study. [12] This study shows the incidence of intraoperative haemorrhage as 0.92%, which is significantly lower than the study by Malik et al [13] (2.86%), but higher than study by Deziel et al (0.25%). There were no bile duct injuries in our study.…”
Section: Intraoperative Complicationscontrasting
confidence: 54%
“…In our experience, most common complications [29] reported portsite bleeding and extraperitoneal insufflations as the most common complications related to access for LC. Subcutaneous emphysema usually is due to leakage of gas from the site of trocar insertion and is more likely to occur when the patient is obese and gas is insufflated through a misdirected Veress needle.…”
Section: Follow-up Assessmentmentioning
confidence: 99%
“…Bu durumu engellemek için değişik yöntemler ve hemostatik ajanlar kullanılmıştır. Trokar yerine uygun Surgicel (Johnson & Johnson Medical, Inc., Arlington, Texas) tampon kullanımı önerilmiştir 11 . Ayrıca trokar yerine foley kateter yerleştirilerek şişirilir ve aynı zamanda yumuşak bir çekiş ile tamponad uygulanabilir.…”
Section: Discussionunclassified